Types and temperaments : personality correlates of belief in, and involvement with paranormal phenomena : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Yapp, Maria Madelene (Massey University, 1995)
The objective of the study reported in this thesis was to investigate personality correlates of belief in, and involvement with paranormal phenomena. Two approaches to personality were adopted. One approach used Jung's (1921/1974) Functional theory of personality types, the other approach used Keirsey and Bates' (1984) four-temperament theory. Belief in the paranormal and involvement with the paranormal were regarded as two distinct and separable variables. Since the mid 1930's there have been over 150 published articles concerned with the various correlates of belief in, and involvement with paranormal phenomena. This reflects the fact that paranormal beliefs in the general population are pervasive and, if religious beliefs are regarded as falling within the domain of paranormal beliefs, are long standing and socially maintained and encouraged. In fact, across cultures, the majority of the population believes in one or more paranormal beliefs (Clarke, 1991; Messer & Griggs, 1989; Sobal & Emmons, 1982, cited in Irwin, 1993). The amount of research data in paranormal beliefs accumulated so far is considered to be substantial (Irwin, 1993).
Keywords: Parapsychology; Human behavior